A crítica da religião em MARX: 1840-1846. - Silva, Romero Junior Venancio (2010)
This thesis has the aim to present and discuss Marx´s criticism to religion in his writings between 1840 and 1846. It divided into two parts. In the first part we worked on the theoretical base which are present in the construction to the marxist criticism to religion. We started from materialism/atomicism by Demócrito and Epicuro, though the satiric criticismo of religion by Luciano and Voltaire up to the religion conception of german idealism by Hegel and Feuerbach. In the second part we analysed Marx´s texts, religion done by the western theologicalmetaphysical thought to socio-political realm. The german philosopher begins a modern criticism of religion and opens a new horizon for social theory in the religious phenomena studies.